The association between estimated average glucose levels and fasting plasma glucose levels - Giray Bozkaya; Emrah Ozgu; Baysal Karaca (Clinics, 2010)
OBJECTIVE: The level of hemoglobin A1c (HbA1c), also known as glycated hemoglobin, determines how well a patient's blood glucose level has been controlled over the previous 8-12 weeks. HbA1c levels help patients and doctors understand whether a particular diabetes treatment is working and whether adjustments need to be made to the treatment. Because the HbA1c level is a marker of blood glucose for the previous 120 days, average blood glucose levels can be estimated using HbA1c levels. Our aim in the present study was to investigate the relationship between estimated average glucose levels, as calculated by HbA1c levels, and fasting plasma glucose levels. METHODS: The fasting plasma glucose levels of 3891 diabetic patient samples (1497 male, 2394 female) were obtained from the laboratory information system used for HbA1c testing by the Department of Internal Medicine at the Izmir Bozyaka Training and Research Hospital in Turkey. These samples were selected from patient samples that had hemoglobin levels between 12 and 16 g/dL. The estimated glucose levels were calculated using the following formula: 28.7 x HbA1c - 46.7. Glucose and HbA1c levels were determined using hexokinase and high performance liquid chromatography (HPLC) methods, respectively. RESULTS: A strong positive correlation between fasting plasma glucose levels and estimated average blood glucose levels (r=0.757, p<0.05) was observed. The difference was statistically significant. CONCLUSION: Reporting the estimated average glucose level together with the HbA1c level is believed to assist patients and doctors determine the effectiveness of blood glucose control measures.